Hubungan antara Iklim Kampus dengan Student Engagement pada Mahasiswa Karyawan Fakultas Psikologi Universitas X - Meme Normasari; Amin Al Adib; Ria Rizkiyana (Prosiding Seminar Nasional Ilmu Kesehatan dan Keperawatan, 2025)
Education plays an important role in improving employee performance. Many employees choose to continue their studies in order to hone skills relevant to the needs of the company. In response to this need, universities provide employee class programs. However, employee students face a double challenge, namely performing the roles of worker and learner, which can potentially cause role conflict. One external factor that influences their success in college is the campus climate. A conducive campus climate can enhance students' success in the learning process. This study aims to investigate the relationship between campus climate and student engagement among employee students at the Faculty of Psychology, University X. The hypothesis proposed in this study is that there is a positive relationship between campus climate and student engagement among employee students at the Faculty of Psychology, University X. The research subjects were 140 working students selected using convenience sampling. The research instruments consisted of a campus climate scale and a student engagement scale. Data analysis was conducted using Pearson's correlation. The results of the study showed a correlation coefficient of r = 0.105 with p = 0.216 (p > 0.05), meaning the hypothesis was rejected because there was no significant relationship between campus climate and student engagement among working students. This finding suggests that other factors outside of campus climate may play a more significant role in shaping working students engagement.